2019
DOI: 10.1016/j.cell.2019.07.031
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic Action of NRF2 Depends on De-glycation by Fructosamine-3-Kinase

Abstract: Fructosamine-3-kinase promotes hepatocellular carcinoma by mediating deglycation of NRF2, a protein modification process previously understudied for cellular proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(144 citation statements)
references
References 73 publications
3
141
0
Order By: Relevance
“…Extracellular signal-regulated protein kinases (ERK) [24], c-jun N-terminal kinase (JNK) [24], PI3K-AKT [19], protein kinase C (PKC) [25], casein kinase 2 (CK2) [26], and protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK) [27] were reported to mediate phosphorylation of NRF2 and increase its stability and subsequent transcriptional activity, whereas p38 and GSK3-mediated phosphorylation of NRF2 decreases NRF2 stability [19]. In hepatocellular carcinoma triggered by MYC and KEAP1 inactivation, fructosamine-3-kinase (FN3K), a kinase that triggers protein de-glycation, mediates NRF2 de-glycation that stabilizes NRF2 and executes its oncogenic function [28].…”
Section: Regulation Of Nrf2 Protein Stabilitymentioning
confidence: 99%
“…Extracellular signal-regulated protein kinases (ERK) [24], c-jun N-terminal kinase (JNK) [24], PI3K-AKT [19], protein kinase C (PKC) [25], casein kinase 2 (CK2) [26], and protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK) [27] were reported to mediate phosphorylation of NRF2 and increase its stability and subsequent transcriptional activity, whereas p38 and GSK3-mediated phosphorylation of NRF2 decreases NRF2 stability [19]. In hepatocellular carcinoma triggered by MYC and KEAP1 inactivation, fructosamine-3-kinase (FN3K), a kinase that triggers protein de-glycation, mediates NRF2 de-glycation that stabilizes NRF2 and executes its oncogenic function [28].…”
Section: Regulation Of Nrf2 Protein Stabilitymentioning
confidence: 99%
“…Glycation is increasingly seen as a driver of metabolic disease and aging, and it may elicit specific effects by targeting signaling proteins (Chaudhuri et al, 2018;Kold-Christensen and Johannsen, 2020). In this context, glycation of the ryanodine receptor associated with successive Ca 2+ leakage and mitochondrial damage (Ruiz-Meana et al, 2019), reversible inhibitory glycation of nuclear factor erythroid 2-related factor 2 (Nrf2) (Sanghvi et al, 2019), and methylglyoxal-induced dimerization of Kelch-like ECH-associated protein 1 (KEAP1) with subsequent activation of the KEAP1/Nrf2 transcriptional program (Bollong et al, 2018) have been reported. The latter may play a role in the upregulation of defense systems, such as GLO1 and the ubiquitin-proteasome system (UPS), and may be involved in the hormetic effect of methylglyoxal (Ravichandran et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Glycation is reversible, which is mediated by Fructosamine-3-kinase (FN3K). Sanghvi et al found that glycation of NRF2 decreased both protein stability and small musculoaponeurotic fibrosarcoma (MAF) protein binding, thereby reducing NRF2 transcriptional output [ 110 ]. This study suggests that NRF2 responds to sugar availability and that targeting FN3K may be a potential therapeutic strategy for NRF2 active cancers.…”
Section: Metabolic Pathways That Stabilize Nrf2mentioning
confidence: 99%